Development Of Tafseer Of The Quran In Surah Al-Baqarah Verse 83 On Islamic Education In Indonesia - Mahardhika, Muhammad Fajrul; Wantini, Wantini; Alee, Andunrorma (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
The current interpretation of the Al-Qur'an has the impact of shifts or changes in education creating problems with its integrity. This research aims to determine the development of Al-Quran Tafsir in Surah Al-Baqarah verse 83 towards Islamic Education in Indonesia. This research uses library research methods. This research will examine various library sources that are the main issues being discussed. What is clearer is to examine the development of the interpretation of the Qur'an on Islamic education, what is in Surah al-Baqarah verse 83: a study of the interpretation of Ibn Katsir written by Ibnu Katsir and Tafsir al-Maraghi written by al-Maraghi, although some In his interpretation, he also uses verses, but he uses ro'yi more dominantly. From the results of this research, we can conclude that the development of Al-Quran interpretation in Surah Al-Baqarah Verse 83 towards Islamic education in Indonesia involves the history and dynamics of writing interpretations, and is influenced by various factors such as changing times, changes in thinking, and changes in social structure. The development of Al-Quran interpretation in Indonesia has had a significant impact on people's thinking, both in terms of improving the quality of Al-Quran interpretation, the influence of Islamic reform, and the dynamics of writing Al-Quran interpretations which influence various aspects of people's thinking.